EVALUASI PROGRAM PKK DALAM PEMBERDAYAAN PEREMPUAN DESA GEMBARAN - Putri Rosmitha; Raju Maulana; Yaswar Aprilian (Indragiri Research Center (ingreat), 2026)
This study aims to evaluate the management of the PKK program in empowering women in Gembaran Village. The focus of this research includes program planning, implementation, and supervision or control of PKK activities in improving women's capacity and independence in rural communities. This research uses a qualitative approach with a descriptive-evaluative research design. The research informants consisted of PKK administrators, the village head, and PKK members who actively participate in women's empowerment activities. Data were collected through in-depth interviews, observation, and documentation. Data analysis employed the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that PKK program planning has been carried out through the preparation of work plans adjusted to community needs. Program implementation includes skills training, health education, and social activities that encourage women's participation. Program supervision is conducted through monitoring activities and routine evaluations by PKK administrators. Overall, the PKK program in Gembaran Village has contributed positively to improving women's knowledge, skills, and participation in community social activities, although several obstacles remain such as limited funding and uneven participation among members.